COMPARISION OF ANALGESIC EFFICACY OF ROPIVACAINE VERSUS BUPIVACAINE IN ULTRASOUND GUIDED BILATERAL ERECTOR SPINAE BLOCK IN LAPAROSCOPIC CHOLECYSTECTOMY: RANDOMIZED CLINICAL TRIAL - HASSARADDI, GEETHA S.; SD, PRATIBHA; VADIGERI, PRASHANTH; JN, SHYNEE; BABU, RAMESH (International Journal of Current Pharmaceutical Research, 2025)
Objective: Laparoscopic cholecystectomy (LC) is the primary treatment for cholelithiasis and is minimally invasive surgery, but common adverse effects is post-operative pain. Our study aims to assess the analgesic effect of Erector spinae plane block (ESPB) guided by ultrasound for post-operative pain and the need for rescue analgesia following laparoscopic cholecystectomy. Methods: Eighty patients were included in the study who were scheduled for laparoscopic cholecystectomy with 40 patients in each group. Patients were randomly assigned to one of the two groups who underwent ESPB prior to surgery: Group B (ESPB with 20 ml of 0.25% Bupivacaine) or Group R (ESPB with 20 ml of 0.375% Ropivacaine). Pain assessment was done for 24 h postoperatively. Patients received Tramadol 1 mg/kg intravenously as a rescue analgesic if their Numerical rating scale (NRS) was ≥4. Results: Group R had lower mean NRS at 1 h, 3 h, 6 h, and 24 h, and Inj tramadol as rescue analgesia was less than in Group B. Conclusion: Ropivacaine 0.375% provided better pain relief in post-operative period, lesser need for analgesia, lower dose of Tramadol requirement in comparison to Bupivacaine 0.25% in ultrasound-guided Erector spinae block.